Simplify the expression:  `(2sqrt(3)sqrt(36))`   2 square root 3 square root 36

Expert Answers

An illustration of the letter 'A' in a speech bubbles

As user durbanville says, a square root can have a negative or positive result.

So `2sqrt(3)sqrt(36) = 2(-sqrt(3))(-sqrt(36))` or `2(-sqrt(3))(+sqrt(36))` or `2(+sqrt(3))(-sqrt(36))` or `2(+sqrt(3))(+sqrt(36))`

Now `sqrt(36) = sqrt(6^2) = (6^2)^(1/2) = 6^(2(1/2)) = 6`

So `2sqrt(3)sqrt(36) = +2(6)sqrt(3)` or `-2(6)sqrt(3)` or `-2(6)sqrt(3)` or `+2(6)sqrt(3)`

Only two of these are unique so

`2sqrt(3)sqrt(36) = +2(6)sqrt(3)` or `-2(6)sqrt(3)`

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

`2sqrt(3) sqrt(36)` is not an equation so you can only simplify it. To be an equation, it would have an equal sign (=) and a variable (such as 'x' to solve).

`2sqrt(3) sqrt(36)`      A square root can have a negtive or positive result

= `2sqrt3. 6`  or `2sqrt(3) (-6)`

= `12sqrt(3)` or `-12sqrt(3)`

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial